Is household composition associated with the presence of risk behaviors in Brazilian adolescents? - Marielly Rodrigues de Souza; Ana Paula Muraro; Amanda Cristina de Souza Andrade; Márcia Gonçalves Ferreira; Paulo Rogério Melo Rodrigues (Revista Brasileira de Epidemiologia)
ABSTRACT Objective: To analyze the association of household composition with risk behaviors in Brazilian adolescents. Methods: Cross-sectional study, with a nationally representative sample of Brazilian adolescents (n=159,245) aged 13 to 17, enrolled and regularly attending the 7th to 9th year of elementary school and the 1st to 3rd year of high school, participants in the National Survey of School Health in 2019. The risk behaviors were: insufficient physical activity, sedentary behavior, alcohol consumption, smoking, poorer diet quality, skipping breakfast and not having meals with parents/guardians. In the analyses, the sampling weights and study design were considered, stratified by the type of school (public or private) and estimated using Poisson regression models. Results: Adolescents, from public and private schools, who lived in single-parent households or where parents were absent, had a higher prevalence of alcohol consumption, smoking, poorer diet quality, skipping breakfast and not eating meals with parents/guardians, compared to those who lived with both parents. Additionally, adolescents from public schools showed a higher prevalence of sedentary behavior than those from single-parent households. Adolescents from private schools had a higher prevalence of sedentary behavior among those who lived only with their mother and a higher prevalence of insufficient physical activity among those who lived without either parent. Conclusion: Brazilian adolescents, from public and private schools, who lived in single-parent households or without parents, showed higher prevalence of risk behaviors.